If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + -2y)(8 + -1y) = 0 Multiply (3 + -2y) * (8 + -1y) (3(8 + -1y) + -2y * (8 + -1y)) = 0 ((8 * 3 + -1y * 3) + -2y * (8 + -1y)) = 0 ((24 + -3y) + -2y * (8 + -1y)) = 0 (24 + -3y + (8 * -2y + -1y * -2y)) = 0 (24 + -3y + (-16y + 2y2)) = 0 Combine like terms: -3y + -16y = -19y (24 + -19y + 2y2) = 0 Solving 24 + -19y + 2y2 = 0 Solving for variable 'y'. Factor a trinomial. (3 + -2y)(8 + -1y) = 0Subproblem 1
Set the factor '(3 + -2y)' equal to zero and attempt to solve: Simplifying 3 + -2y = 0 Solving 3 + -2y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = 0 + -3 -2y = 0 + -3 Combine like terms: 0 + -3 = -3 -2y = -3 Divide each side by '-2'. y = 1.5 Simplifying y = 1.5Subproblem 2
Set the factor '(8 + -1y)' equal to zero and attempt to solve: Simplifying 8 + -1y = 0 Solving 8 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = 0 + -8 -1y = 0 + -8 Combine like terms: 0 + -8 = -8 -1y = -8 Divide each side by '-1'. y = 8 Simplifying y = 8Solution
y = {1.5, 8}
| (y-9)(y+9)= | | (m+1)(m+1)= | | (a-5)(a+3)= | | 3r(r-5)-2r(3r-1)= | | -2a(3a^2-4a-1)= | | 5(2x-11)+17=52 | | 5x(4x-3)= | | 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 | | x=12+9 | | 45/18=9/x | | -4/5*(4*-34/4-1) | | (2)/(2x-5)=-2 | | -1/4x^2-x-8=0 | | -34/4 | | 2x+5x=-15x-6x | | x/6=12/8 | | 20/16=70/x | | 6/12=n/42 | | -4/5*(4a-1)=28 | | F(x)=-3x-8f(2) | | 5+4/x | | 3/x+2/5 | | 5/x-2/x |